ANALISIS FAKTOR KONSELING KELUARGA BERENCANA TERHADAP PEMILIHAN METODE KONTRASEPSI PADA PASANGAN USIA SUBUR DI UPTD PUSKESMAS LUMBAN LOBU KECAMATAN BONATUA LUNASI KABUPATEN TOBA TAHUN 2025 - Mastaida Tambun; Necia Pratilia Siagian; Siti Nurmawan Sinaga; Herna Rinayanti Manurung (Ensiklopedia Research and Community Service Review, 2026)
Background The high population growth rate in Indonesia remains a serious concern, one of which is addressed through the Family Planning (FP) program. The selection of contraceptive methods among couples of reproductive age (CRA) is influenced not only by the availability of contraceptive methods but also by the quality of counseling provided by healthcare professionals. Effective counseling plays an important role in helping individuals understand various contraceptive methods, including their benefits, contraindications, and side effects, enabling them to make rational and voluntary decisions. Objective This study aims to analyze the influence of family planning counseling on the selection of contraceptive methods among CRA at UPTD Puskesmas Lumban Lobu, Bonatua Lunasi District, Toba Regency in 2025. Methods This research used a quasi-experimental design with a pretest-posttest control group approach. The sample consisted of 67 respondents selected using purposive sampling. The research instrument was a questionnaire, and data were analyzed using the paired sample t-test. Results The study found that family planning counseling had a significant effect on contraceptive method selection. Most respondents experienced improved understanding and changes in decision-making after receiving counseling. Conclusion Family planning counseling significantly improves knowledge, decision-making, and contraceptive method selection among couples of reproductive age. Effective counseling helps respondents understand the types, benefits, and side effects of contraceptives, enabling them to choose the method most suitable for their needs. Suggestion Healthcare providers are encouraged to enhance the quality of FP counseling using a more communicative and client-centered approach. Couples of reproductive age are also encouraged to actively seek information and participate in counseling sessions before deciding on a contraceptive method.Keywords: Family Planning Counseling, Contraceptive Method Selection, Couples of Reproductive Age, Family Planning Program